2001
DOI: 10.1017/s1355838201001200
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in the prp12 + gene encoding a homolog of SAP130/SF3b130 causes differential inhibition of pre-mRNA splicing and arrest of cell-cycle progression in Schizosaccharomyces pombe

Abstract: ABSTRACTprp12-1 is one of the mutants defective in pre-mRNA splicing at a nonpermissive temperature in Schizosaccharomyces pombe. We found that the prp12 + gene encodes a protein highly homologous with a human splicing factor, SAP130/SF3b130, a subunit of a U2 snRNP-associated complex SF3b. Prp12p was shown to interact genetically with Prp10p that is a homolog of SAP155/SF3b155, another subunit in SF3b, suggesting that Prp12p is a functional homolog of human SAP130/SF3b130. Prp12p tagged with GFP is uniformly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…These include the mutants cdc5, cdc28 and prp12, all of which appear to arrest in G2 upon shift to the restrictive temperature (Burns et al, 1999;Habara et al, 2001;Ohi et al, 1994). It has also been reported that cdc5 mutants, in the absence of Wee1, undergo mitotic catastrophe similar to what we observe following depletion of Ini1 (Ohi et al, 1994).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…These include the mutants cdc5, cdc28 and prp12, all of which appear to arrest in G2 upon shift to the restrictive temperature (Burns et al, 1999;Habara et al, 2001;Ohi et al, 1994). It has also been reported that cdc5 mutants, in the absence of Wee1, undergo mitotic catastrophe similar to what we observe following depletion of Ini1 (Ohi et al, 1994).…”
Section: Resultssupporting
confidence: 85%
“…At least three of these genes, cdc5, cdc28 and prp12 + are required for cell viability and cell cycle progression (Habara et al, 2001;Lundgren et al, 1996;Ohi et al, 1994). Furthermore, a Saccharomyces cerevisiae homologue of ini1 + is present in purified preparations of the yeast U2/U5/U6 snRNP complex, which is required for pre-mRNA splicing (K. Gould, personal communication).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are introns which are spliced independently of the large subunit of the U2 auxiliary factor (U2AF 59 ). Noteworthy here, U2AF 59 is essential for growth [56][57][58]. Moreover, there is some evidence that the recruitment of U2AF 59 to auxiliary factor dependent introns might be mediated by the SR protein Srp2, which has been shown above to be an in vitro substrate of Prp4 kinase [26].…”
Section: Inhibition Of Prp4 Kinase Activity Affects Splicing Of Intromentioning
confidence: 79%
“…Links between splicing events and cell cycle regulation that involve Prp8 and other splicing components have been reported in budding and fission yeast, while in Drosophila, orthologs of the splicing factors that suppress cdc-25.1(rr31) affect cell growth, supporting the idea that the links between splicing and cell cycle control may have been conserved from yeast to higher eukaryotes (Shea et al 1994;Lundgren et al 1996;Potashkin et al 1998;Ben-Yehuda et al 2000a,b;Russell et al 2000;Habara et al 2001;Coelho et al 2005).…”
Section: Links Between Splicing Events and Cell Cycle Regulationmentioning
confidence: 86%